Application of alternative correctives in salinized soil with cultivation of Sorghum bicolor L - Albuquerque, Alciênia Silva; Fonsêca, Nathan Castro; Santos, Rivaldo Vital dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
In semi-arid regions, irrigation is a constant and necessary practice for the cultivation of some plant species, but poor management favors the degradation of physical and chemical properties of soil due to the salinization process, causing low productivity and land abandonment. Therefore, this study aimed to evaluate the efficiency of the application of gypsum and alternative coproducts in the recovery of saline soils and the possible cultivation of Sorghum bicolor (L. Moench). We performed an experiment in a factorial design 2x2x5, consisting of two levels of gypsum (absence and presence), two levels of co-product (vermiculite + bovine manure and kaolin + bovine manure) and five doses of each compound (0, 15, 30, 45 and 60%) volume per pot (v:v). Each treatment was replicated three times, totaling 60 vessels with a capacity of 9 L. After corrective and compounds application we sown ten seeds of Sorghum bicolor per vase. Fifteen days after the germination we perform the thinning maintaining three plants per pot. We evaluated the chemical characteristics of the soil and plant growth parameters, such as height, number of leaves, collar diameter, shoot fresh mass, shoot dry mass and root dry mass. We verified that the corrective application improved the chemical attributes of the soil allowing degraded and abandoned areas to be productive again. We recommended the application of the co-product kaolin with cattle manure, what favor the initial growth of the species Sorghum bicolor constituting an efficient alternative to minimize the harmful effects of salinity caused to the soil, environment, and productivity.